Factor VIII Inhibitor Antibodies with C2 Domain Specificity Are Less inhibitory to Factor VIII Complexed with von Willebrand Factor - Suzuki, Suzuki; Arai, Morio; Amano, Kagehiro; Kagawa, Kazuhiko; Fukutake, Katsuyuki (Thrombosis and Haemostasis, 1996)
In order to clarify the potential role of von Willebrand factor (vWf) in attenuating the inactivation of factor VIII (fVIII) by those antibodies with C2 domain specificity, we investigated a panel of 14 human antibodies to fVIII. Immunoblotting analysis localized light chain (C2 domain) epitopes for four cases, heavy chain (A2 domain) epitopes in five cases, while the remaining five cases were both light and heavy chains. The inhibitor titer was considerably higher for Kogenate, a recombinant fVIII concentrate, than for Haemate P, a fVIII/vWf complex concentrate, in all inhibitor plasmas that had C2 domain specificity. In five inhibitor plasmas with A2 domain specificity and in five with both A2 and C2 domain specificities, Kogenate gave titers similar to or lower than those with Haemate P. The inhibitory effect of IgG of each inhibitor plasma was then compared with recombinant fVIII and its complex with vWf. When compared to the other 10 inhibitor IgGs, IgG concentration, which inhibited 50% of fVIII activity (IC50), was remarkably higher for the fVIII/vWf complex than for fVIII in all the inhibitor IgGs that had C2 domain reactivity. Competition of inhibitor IgG and vWf for fVIII binding was observed in an ELISA system. In 10 inhibitors that had C2 domain reactivity, the dose dependent inhibition of fVIII-vWf complex formation was observed, while, in the group of inhibitors with A2 domain specificity, there was no inhibition of the complex formation except one case. We conclude that a subset of fVIII inhibitors, those that bind to C2 domain determinants, are less inhibitory to fVIII when it is complexed with vWf that binds to overlapping region in the C2 domain.